Policies and actions for electric vehicle battery waste processing using an integrated QFD approach: A case study for Jordan - Fadwa Dababneh; Hussam Zuhair Aldababneh; Mohamad K. Khawaja; Rana Imam (Heliyon)
Electric vehicles (EVs) are regarded as a key technology to fight climate change. However, with the increasing popularity of EVs, comes the challenge of handling spent EV batteries. Despite considerable research on end-of-life (EOL) methods, economics, and environmental benefits, many countries are facing challenges with the formulation of policies and proactive response actions needed for robust EOL infrastructure. There is a lack of research that employs comprehensive and systematic methods for identifying and prioritizing stakeholder needs, tradeoffs, and preferences. Accordingly, in this paper, a modified Quality Function Deployment approach is employed to prioritize actions, recommendations, and policies that address the handling of the spent batteries. The proposed method is applied on Jordan and a course of action and policies are proposed that will allow for the integration of adequate and appropriate EOL strategies. For Jordan, the most stringent needs revolve around the development of a collection center for EOL batteries and an incentive-based return process. Moreover, policy implications for the immediate, medium, and long-term horizons for Jordan were outlined.